Effectiveness of Prophylactic Bolus Ephedrine Versus Norepinephrine for Management of Postspinal Hypotension during Elective Caesarean Section in Resource Limited Setting: A Prospective Cohort Study - Mitiku Desalegn; Tewoderos Shitemaw; Habtamu Tamrat (Anesthesiology Research and Practice)
Background. Spinal anaesthesia for caesarean section is the preferred technique since it provides better maternal safety and neonatal outcome compared to general anaesthesia. Hypotension is the most common complication after spinal anaesthesia. The study aims to determine the effectiveness of a prophylactic bolus dose of norepinephrine and ephedrine on the management of postspinal hypotension during caesarean section. Method. An institutional-based prospective cohort study was conducted on 84 pregnant women undergoing elective caesarean section. Based on the responsible anaesthetist’s postspinal hypotension management plan, patients were divided into two groups. Those patients who received ephedrine are grouped into the ephedrine (EPH, n = 42) group, and patients who received norepinephrine are grouped under the norepinephrine group (NE, n = 42) by data collectors. After aseptic technique, spinal anaesthesia was administered with 0.5% (3 ml) bupivacaine using a 23G spinal needle. During spinal anaesthesia, a prophylactic bolus dose of 10 mg (2 ml) EPH or 16 g (2 ml) NE was given based on management plan of the shift anaesthetist. Mean arterial pressure (MAP), the heart rate (HR), number of boluses of vasopressor used, incidence of nausea and vomiting, and the Apgar score of babies at 1 and 5 min between the groups were recorded. Results. The norepinephrine group had a statistically significant higher MAP compared to the ephedrine group in the first 10 and 15 min (p<0.05) of the study period. Thereafter, there was no statistically significant difference in MAP between the groups until the end of the study period (p>0.05). The ephedrine group had a statistically significant higher heart rate throughout the procedure compared to the norepinephrine group (p<0.05). The norepinephrine group required a lower bolus number of vasopressors compared to the ephedrine group to maintain blood pressure. The Apgar scores of all babies at 1 and 5 min were above seven. Significant differences regarding maternal complications (nausea and vomiting) between the groups were not detected (nausea, p=0.21 and vomiting, p=0.092). Conclusion. Norepinephrine can be used instead of ephedrine to keep a pregnant mother’s blood pressure stable during a caesarean section under spinal anaesthesia without causing harm to the mother or baby. Trial registration. ClinicalTrials.gov Identifier: NCT05522088 (Date of registration: 30/08/22).